2017
DOI: 10.1097/naq.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Impact of Nurse Manager Large Spans of Control

Abstract: Nurse managers are instrumental in achievement of organizational and unit performance goals. Greater spans of control for managers are associated with decreased satisfaction and performance. An interprofessional team measured one organization's nurse manager span of control, providing administrative assistant support and transformational leadership development to nurse managers with the largest spans of control. Nurse manager satisfaction and transformational leadership competency significantly improved follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 12 publications
3
57
0
2
Order By: Relevance
“…Reports of two interventions from the UK (Locke et al, ) and the United States (Simpson et al, ) support the intent of the intervention reported in this paper. In a study evaluating the introduction of administrative assistants in the UK, ward managers reported a reduction in workload and greater job satisfaction (Locke et al, ).…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Reports of two interventions from the UK (Locke et al, ) and the United States (Simpson et al, ) support the intent of the intervention reported in this paper. In a study evaluating the introduction of administrative assistants in the UK, ward managers reported a reduction in workload and greater job satisfaction (Locke et al, ).…”
Section: Introductionsupporting
confidence: 68%
“…Recommendations from the reviews included measures to reduce the bureaucratic administrative burden for the NUM role and the need for clinical leadership education and mentoring (Queensland Government, , ). The state‐wide review findings are not unique and are consistent nationally (Duffield et al, ; Gaskin, Ockerby, Smith, Russell, & O'Connell, ) and internationally (Gunawan et al, ; Loveridge, ; Simpson et al, ; Udod et al, ; Wong & Laschinger, ).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations